PUBLIC ENVIRONMENTAL MONITORING OF DRINKING WATER QUALITY IN THE CITY OF NORILSK - N. V. Karmanovskaya (Academic Scientific Journal of Chemistry, 2021)
According to UN estimates, the shortage of safe drinking water can become one of the most acute and pressing problems. The specificity of this problem for Russia is not a shortage of water resources, but their pollution and ongoing degradation of water bodies. The quality of water is understood as the totality of its properties associated with the nature and concentration of impurities in the water. Water analysis is the only tool for monitoring its condition and properties. During the experiment, a team of researchers took samples of drinking water from the water supply network in various districts of the Norilsk industrial region, studied the dependence of the quality characteristics of water on the location and sampling method. Based on the findings, conclusions on the quality of drinking water were drawn. During the experiment, the authors found that in terms of organoleptic indicators, drinking water in all areas of the NIR meets the requirements of Sanitary Rules and Regulations and GOST. Taking samples at three control points of the Norilsk industrial region, it has been proven that the water is soft and its salt content is mainly due to the presence of hardness salts. Having made the necessary analyses, the authors found that the presence of microorganisms in the water supply network of the NIR is not significant, the permanganate oxidisability indicator does not exceed the requirements of Sanitary Rules and Regulations